'A relationship of mutual exploitation': the evolving ties between the Pentagon, Hollywood, and the commercial gaming sector. (4th July 2019) - Kaempf, Sebastian
ABSTRACT: This article examines the close historical and contemporary ties between the Pentagon and Hollywood from the 1920s until today. Drawing on the US military as an in-depth case study, the article shows the extent to which key military actors view the conduct of war as an arena that stretches well beyond the actual battlefields and includes the production of war movies, film documentaries, computer simulations and first person shooter video games. The article begins with an examination of the 'Military-Industrial Complex' and its evolution into what experts have dubbed 'The Military-Industrial-Media-Entertainment Network (MIME-Net).' It then focuses on the military's relationship with the filming industry, with the production of reality TV, and the commercial gaming industry. It thereby investigates, through in-depth interviews with key stakeholders, how this phenomenon has evolved over time and into new areas where games, simulators, and game technologies cross the boundaries between militaries, the defense industry, Hollywood and the commercial gaming sector. And it shows how the advent of digital new technologies have opened new platforms through which militaries seek to boost recruitment, to (re)write military history, and to influence the portrayal of the armed forces in the eyes of the public.